Examining the traditional waqf-based financing methods and their implications on socio-economic development - Ahmed, Umar; Mohamed, Mustafa Omar; Ogunbado, Ahamad Faosiy (International Organisation of Scientific Research (IOSR), 2015)
Waqf properties constitute a large percentage of societal wealth in several Muslim countries. Yet, many Muslim countries are facing enormous socio-economic problems such as poverty, illiteracy and lack of basic healthcare services. These socio-economic problems encourage contemporary Muslim scholars to revive the traditional methods of financing the development ofwaqf properties to ensure that waqf institution plays its vital role onimproving the social welfare of the ummah. This paper examines the traditional waqf-based financing methods of developing waqf properties and their implications on socio-economic development. We have realized that with goodwaqf management and effective legislations, istibdal could be more suitable for the development of waqf properties, which in turn will finance socio-economic development. Nevertheless, all the traditionalwaqf-basedfinancing methods may not be suitable in most of the low income Muslim countries, as there are widespread corruption and abuses of waqf properties. Therefore, allowing the waqf management to develop waqf assets using these traditional methods may expose waqf assets to further abuses and expropriation. The paper suggests that, putting the right waqf management teams which practices good governance; cash waqf, waqf share scheme and corporate waqf would be the most suitable methods of financing both the development of waqf properties as well as socio-economic development.